Exercise training at high altitude: Does it improve endurance performance at sea level? - Sutton, R. J. (1993)
1. As altitude increases, the barometric pressure and the oxygen partial pressure decrease. This means that any athletic performance critically dependent on oxygen for metabolism, i.e., any event lasting longer than roughly two minutes, might be adversely affected. By contrast, because the air at high altitude is less dense than at sea level, jumping, sprinting, and other activities in which air resistance needs to be overcome might be enhanced when competing at high altitude. 2. The most important physiological adaptations to living at high altitude are increased ventilation of the lungs, increased blood hemoglobin, and enhanced extraction of oxygen by the tissues. Maximal cardiac output is not usually affected by altitude. 3. Although acclimatization to or residence at high altitude is required for optimal endurance performance at high altitude, the value of high altitude training for endurance performance at sea level has yet to be proven. 4. Nutrition for athletes at altitude can be a major problem, and weight loss will be significant at moderate to high altitudes. The amount of weight loss is generally dependent on the absolute altitude.